Analisis Pengaruh Kredibilitas Financial Technology, Literasi Keuangan, Dan Literasi Financial Technology Terhadap Intensitas Penggunaan Fintech (Studi Kasus Pada Generasi Z Wilayah Karesidenan Pekalongan) - Mu'aliyah, Ni'mah Mu'aliyah (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2025)
This study aims to analyze the effect of financial technology credibility, financial literacy, and financial technology literacy on the intensity of Fintech use among users in the Pekalongan Prefecture. The study used a quantitative approach with multiple linear regression analysis techniques to test the relationship between the independent and dependent variables. The results showed that financial technology credibility and financial technology literacy have a significant influence on the intensity of Fintech use, while financial literacy has no significant effect. The contribution of these variables to the intensity of Fintech use reached 22.1%, with financial technology credibility and literacy being the main driving factors. This study emphasizes the importance of improving financial education and strengthening trust in Fintech services to encourage wider adoption of financial technology.